Effects of Medlax on anxiety of spouses of patients in the intensive care unit - Novela, Hazel E. (1997)
A general framework of MEDLAX- an intervention comprising of meditation, relaxation combined with music was tested among spouses of patients in the ICU to determine reduction in anxiety levels. Socio-demographic variables (age, sex, education andd income) were hypothesized to affect their anxieties. MEDLAX was hypothesized to have significant relationship, that is, having a direct effect on anxiety levels experienced by spouses during the entire ICU confinement of their husbands/wives. An open-ended question was utilized to determine the perceived causes of anxiety.Quasi experimental design specifically, time series design was utilized. Time series measures were done to determine reduction in anxiety over an extended period (Day 1, Day 2). Two (2) groups of spouses (n=20) were studied. Qualitative and quantitative measures were utilized to analyze the data.The findings of the study are summarized as follows:A. Socio-demographic ProfileThe subjects of the study (n=40) were generally female (72.) with a mean age of 40 years, married, educationally prepared to the college level (50) and has a monthly income of P 6,500-P15,000 (70).B. Causes of anxiety of spouses of patients in the ICUThere were 15 identified causes of anxiety grouped and ranked as follows.Only the major causes are included hereFirst category is Knowledge Deficit (Confusion = 100), followed by the second category which is the Personal and Family Factors (Not being with the patient = 62).The third category is the Communication Factor (Lack of Communication Among Family Members = 50). It was then followed by Nurse-Patient Interaction Factors (Unmet nds 35). The last category is Administrative Factors (Change in visiting hours 28).C. Relationship between Socio-demographic Variables and AnxietyRespondents of the study were spouses ages 21-72 years old with a mean age of 40 years. Pre-intervention anxiety scores of those below 40 years old were higher than those above 40 years old for both groups day 1 and day 2.It was however shown that younger spouses displayed higher level of anxiety as compared to those older and middle adults.
Those who indicated as married have shown moderate levels of anxiety, compared to those who indicated as live-in or separated. Sex and education have no significant correlation with anxiety levels.D. Difference between Control and Experimental Groups.A-State and A-Trait Questionnaire (Spielberger 1966, 1972), measured the anxiety scores of the respondents. Significant results of the paired t-test for days 1 and 2 (t=5.729, p-value 0.00000 and day 2 (t=5.089, p value = 0.00010), for the experimental group indicated a change in anxiety levels utilizing the A-Trait Questionnaire. The pre and post state scores for day 1 and 2 for the control group was not significant (t=1.105, p- value = 0.24950) (t=1.777, p-value=0.24450), respectively.E. Comparison of Pre and Post Intervention Anxiety Scores for both groups for day 1 and 2.The pre-intervention anxiety scores showed that both groups-control and experimental had moderate anxiety (70) and (45), respectively. There was a reduction in post interaction anxiety scores at day 1 for both groups. Spouses in the experimental group showed reduction in post intervention anxiety scores significantly from panic and severe levels to moderate level of anxiety.MEDLAX, as an intervention was repeated on day 2. It has shown an apparent reduction in the scores in day 2 for the experimental group. Those previously in the panic level has apparently been reclassified to the lower level anxiety groups.Implications were derived from the results of the study. The role of the nurse in providing adequate and correct information to the patient and their spouses is emphasized. The study supports the current open policy of allowing spouses/close relations to be with the ICU patients. Despite the limitations of this study, the findings supported the usefulness of MEDLAX in reducing anxiety among spouses of patients. An effective support system can be attained when anxiety situations are better identified and intervention as MEDLAX in reducing anxiety among spouses of patients in the intensive care unit. Recommendations for the use of MEDLAX as a biobehavioral intervention is made.
Thesis (Master of Arts in Nursing)--University of the Philippines Manila.
Keywords: Anxiety; Medlax; Meditation; Relaxation